2021
DOI: 10.1177/17455065211042180
|View full text |Cite
|
Sign up to set email alerts
|

Women’s understanding of economic abuse in North-Western Tanzania

Abstract: Introduction: Economic abuse is a form of intimate partner violence that still lacks a clear conceptualization and therefore is often overlooked next to physical, sexual and psychological abuse. While existing categorizations recognize economic intimate partner violence as economic control, economic exploitation and employment sabotage, current measurements of economic abuse rarely capture all its forms, and the issue has not been widely explored in low- and middle-income country settings. Methods: We conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…As previously noted, economic abuse can be best understood as a mechanism of coercive control (Adams et al, 2020; Dutton et al, 2005; Singh, 2020). de Serpa Pimentel and colleagues (2021) also note that social norms and societal expectations of men and women play a significant role in the occurrence of economic abuse. That is, these abusive behaviors may be more prevalent in societies strongly influenced by gender inequality (González & Rodríguez-Planas, 2020) and patriarchal values and traditions that reinforce male dominance (Mshweshwe, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously noted, economic abuse can be best understood as a mechanism of coercive control (Adams et al, 2020; Dutton et al, 2005; Singh, 2020). de Serpa Pimentel and colleagues (2021) also note that social norms and societal expectations of men and women play a significant role in the occurrence of economic abuse. That is, these abusive behaviors may be more prevalent in societies strongly influenced by gender inequality (González & Rodríguez-Planas, 2020) and patriarchal values and traditions that reinforce male dominance (Mshweshwe, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…behaviors that control a woman’s ability to acquire, use, and maintain economic resources, thus threatening her economic security and potential for self-sufficiency” (Adams et al, 2008, p. 564). Perpetration of economic abuse involves assailants using a wide variety of tactics, including restricting a victim’s access to income, financial information, and other assets; using their partners’ financial resources for their own personal gain, with or without their knowledge (Adams et al, 2020); and preventing their partners from getting or keeping a job (de Serpa Pimentel et al, 2021; Postmus et al, 2016) or pursuing their educational goals (Breckenridge et al, 2014; Riger et al, 2000; Sanders, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A study that was conducted in Mwanza, North-West Tanzania on the understanding of economic abuse against women revealed that women's earnings are controlled by their husbands in some ways; for example, when a husband directs his wife on how to use the money she has. Furthermore, tracking how women spend household income also reflects the less power women have in decision-making (Serpa et al, 2021). Such economic abuse limiting control of women over household resources including their earnings has far-reaching consequences such as household necessities and poverty among women, their families, and society at large.…”
Section: Status Of Women's Control Over Their Earningsmentioning
confidence: 99%
“…Research by Stewart et al (2010;2014) on antenatal and postnatal depressed mood has demonstrated, for instance, the implications of structures of poverty and precarity for the experiences of women and their babies (see also Ng'oma et al 2019). The relationship between economic issues and individual experiences in Malawi underscores how legacies of colonialism and contemporary geopolitical processes can contribute to psychological harm (Johnson et al, 2022;Kanougiya et al, 2021;Serpa Pimentel et al, 2021). and their children to understand other environmental and genetic factors associated with mental ill-health, including any impacts of parental mental health (and its economic and other underpinnings) on infant development.…”
Section: Introductionmentioning
confidence: 99%